Combustion rate catalyst containing metal oxide and preparation method and application thereof

By using a metal oxide skeleton with a pore structure and a spray drying method to prepare a combustion catalyst for spherical particles, the agglomeration and stability of nanometal oxides in the combustion catalyst are solved, and excellent catalytic performance and good dispersion are achieved.

CN116640033BActive Publication Date: 2025-04-18NANJING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310777621.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-04-18
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

Nano-metal oxides have agglomeration and stability problems in the application of combustion rate catalysts, which affect their catalytic properties and dispersion.

Method used

The metal oxide skeleton with a pore structure is used as the combustion speed catalyst, and spherical particles are prepared by spray drying, and combined with high temperature treatment to form a stable metal oxide skeleton structure.

Benefits of technology

It effectively avoids agglomeration of metal particles, improves the stability and catalytic performance of the catalyst, and can be mixed evenly with other pharmaceutical ingredients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116640033B_ABST
    Figure CN116640033B_ABST
Patent Text Reader

Abstract

The present invention discloses a burning rate catalyst and a preparation method and application thereof. The burning rate catalyst utilizes the principle that a spray drying process can obtain micro-nano spherical particles, and uses spray drying as a method for preparing MOFs materials to obtain hollow spherical shells with an average particle size of 2 to 4 μm. The catalyst includes a metal oxide skeleton with a pore structure, which greatly improves the catalytic performance of the calcined product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid propellants and relates to a burning rate catalyst and a preparation method and application thereof. Background Art

[0002] Solid propellant (solid gunpowder) has gradually developed as a composite energetic material for the purpose of propulsion. It mainly provides driving force for rockets, shells, guns, and missiles. It plays a very important role in the development of missiles and aerospace industries. Its performance plays a decisive role in the combat capability of weapons and missiles, and occupies an important position in the national defense science and technology. In order to ensure the ballistic performance of solid rocket engines and the stability of engine operation, most strategies and tactics hope that the burning rate pressure index of solid propellants is low. The burning rate catalyst can play a role in reducing the pressure index of propellants. It is an additive that adjusts the burning rate of propellants through physical or chemical effects. By changing the structure of the combustion wave, the burning rate of the propellant is increased or decreased, which greatly reduces the influence of the pressure index on the burning rate. The amount of addition is usually between 1% and 5% by mass. As an indispensable component in the formulation of solid propellants, the research on burning rate catalysts is an important part of solid propellant research. In recent decades, it has been greatly developed at home and abroad.

[0003] For example, ammonium perchlorate (AP) is widely used as an inorganic oxidant in composite solid propellants (CSPs), and accounts for more than 50wt% of the entire composite solid propellant. Reducing the decomposition temperature of AP and increasing the exothermic energy of AP can accelerate the combustion rate of the propellant and shorten the ignition delay time. Therefore, improving the decomposition of AP is an important factor that directly affects the combustion performance of composite solid propellants. At present, the common method to adjust the speed of AP thermal decomposition is to add burning rate catalysts (BRCs). At present, the commonly used burning rate catalysts are nanometals and their oxides, carbon materials, and nanometal composite particles based on carbon materials. In addition, nanosized metals are often used to catalyze the thermal decomposition of AP due to their small particle size, large specific surface area, and more reaction centers. For example, Fertassi et al. used graphene (G) / CuO and Al / G / CuO composites as potential catalysts for AP thermal decomposition, reducing the high temperature decomposition from 432℃ to 325℃. However, nanometal single oxides are prone to agglomeration, which greatly affects their catalytic performance.

[0004] In fact, the catalytic activity and selectivity of nano catalysts such as copper oxide are much higher than those of traditional catalysts. However, due to the large surface energy and high activity of nano metal oxides, there are two problems in their preparation and use: one is poor dispersibility and easy agglomeration, which causes the actual particles to be much larger when dispersed in the propellant, thereby reducing the catalytic efficiency of the nano particles and failing to fully exert their due catalytic performance; the other is instability, which is easy to crystallize and grow after being placed for a period of time. In this regard, the main method currently used is to modify its surface, such as using azeotropic distillation to replace the hydroxyl groups on the surface of the precursor with organic groups -OSi(CH3)3, -OC4H9, etc., to effectively eliminate the moisture in the wet powder, so that the possibility of chemical bonding between the particle surfaces is greatly reduced, that is, the formation of MOM between the particles is prevented, thereby eliminating the possibility of agglomeration formation; chemically stable and surface coated materials can also be used, but this modification will lead to an increase in particle diameter, and the performance of the coated material cannot be fully exerted. At the same time, due to the large specific gravity of nano metal oxides, they are easy to stratify and difficult to disperse during the mixing process with other drugs, making it difficult to mix them evenly with other drugs.

[0005] Therefore, solving the agglomeration and stability problems encountered by nano-metal oxides in combustion rate catalyst applications has become one of the key technologies for their application and has practical application value and significance. Summary of the invention

[0006] 1. Problem to be solved

[0007] Based on the problems such as agglomeration and stability encountered in the application of existing nano metal oxides in burning rate catalysts; the purpose of the present invention is to provide a burning rate catalyst and a solid propellant containing the burning rate catalyst;

[0008] At the same time, the invention also provides a method for preparing the burning rate catalyst.

[0009] 2. Technical solution

[0010] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0011] A first aspect of the present invention provides a burning rate catalyst, the burning rate catalyst comprising:

[0012] A metal oxide framework having a pore structure;

[0013] Calculated according to the proportion of elements, the weight ratio of metal elements to oxygen elements is (2~2.6): (0.8~1);

[0014] And / or, calculated according to the content of the elements, the metal element accounts for 70-80wt% and the oxygen element accounts for 30-20wt%;

[0015] in,

[0016] The metal includes any one, two, or more than two of copper, cobalt, nickel, and iron;

[0017] Alternatively, the metal oxide includes oxides of any one of copper, cobalt, nickel and iron, or two or more metals.

[0018] According to any embodiment of the first aspect of the present invention, the high temperature treatment has a treatment temperature of 300-500° C. and an atmosphere of air / oxygen.

[0019] According to any embodiment of the first aspect of the present invention, the metal organic framework material is obtained by: a mixed solution containing a metal source and an organic ligand, subjected to spray treatment;

[0020] The number of times of the spraying treatment is ≥2 times.

[0021] According to any embodiment of the first aspect of the present invention, the metal comprises metal one and metal two, and the difference in ionic radius between the metal one and the metal two does not exceed 17 pm;

[0022] The metal is selected from one or both of copper and cobalt;

[0023] The metal is selected from one or more of cobalt, nickel and iron.

[0024] According to any embodiment of the first aspect of the present invention, the burning rate catalyst is spherical;

[0025] The sphere has an average particle size of 2 to 4 μm;

[0026] The spheres are composed of nano-scale metal oxides.

[0027] The second aspect of the present invention provides a method for preparing a burning rate catalyst, comprising the following raw materials:

[0028] Metal sources and organic ligands;

[0029] The steps include:

[0030] S1, preparing a mixed solution containing a metal source and an organic ligand;

[0031] S2, spraying the mixed solution 1 to obtain a dry product;

[0032] S3, subjecting the dried product to high temperature treatment to obtain the burning rate catalyst;

[0033] in,

[0034] In S1, the organic ligand is trimesic acid;

[0035] In S2, the number of spray treatments is ≥ 2 times, preferably 2 to 5 times;

[0036] In S3, the temperature of the high temperature treatment is 300-500° C. and the atmosphere is air atmosphere / oxygen atmosphere.

[0037] According to any embodiment of the second aspect of the present invention, in S2, the process parameters of the spray treatment are as follows:

[0038] Air flow speed 30~40m 3 / h;

[0039] The spray treatment inlet temperature is 170~190℃;

[0040] The feed rate is 1~2ml / min.

[0041] According to any embodiment of the second aspect of the present invention, in S2, the process parameters of the spray treatment are as follows:

[0042] Air flow speed 35~40m 3 / h;

[0043] The spray treatment inlet temperature is 175~185℃;

[0044] The feed rate is 1.2~1.8ml / min.

[0045] According to any embodiment of the second aspect of the present invention, in S2, the process parameters of the spray treatment are as follows:

[0046] Air velocity 38m 3 / h;

[0047] The spray treatment inlet temperature is 180°C;

[0048] The feed rate was 1.5 ml / min.

[0049] According to any embodiment of the second aspect of the present invention, in S2, in the spray treatment process, the actual volume flow rate of the material is 500~600 L / h.

[0050] According to any embodiment of the second aspect of the present invention, in S2, in the spray treatment process, the actual volume flow rate of the material is 510~550 L / h.

[0051] According to any embodiment of the second aspect of the present invention, in S2, in the spray treatment process, the actual volume flow rate of the material is 530~540 L / h.

[0052] According to any embodiment of the second aspect of the present invention, in S1, the molar ratio of the metal source to the organic ligand is (3-1): (3-1).

[0053] According to any embodiment of the second aspect of the present invention, in S1, the metal includes metal one and metal two;

[0054] The amount of the metal source added must satisfy the molar ratio of metal one to metal two of (0-10): (0-10); preferably (1-10): (1-10); more preferably (1-8): (1-8); and most preferably (1-5): (1-5).

[0055] According to any embodiment of the second aspect of the present invention, in S3, the high temperature treatment time is 1 to 3 hours.

[0056] According to any embodiment of the second aspect of the present invention, S2 comprises:

[0057] spraying the mixed solution to obtain a dry product;

[0058] preparing a second mixed solution containing a dry product;

[0059] The mixed solution 2 is sprayed to obtain a dry product.

[0060] The third aspect of the present invention provides a solid propellant, the solid propellant containing the burning rate catalyst according to any embodiment of the first aspect of the present invention; or the burning rate catalyst prepared by the method according to any embodiment of the second aspect of the present invention;

[0061] or,

[0062] The solid propellant contains the burning rate catalyst described in any embodiment of the first aspect of the present invention; or the burning rate catalyst prepared by the method described in any embodiment of the second aspect of the present invention; and ammonium perchlorate.

[0063] A fourth aspect of the present invention provides an application of a burning rate catalyst, which is used as a burning rate catalyst for ammonium perchlorate.

[0064] Beneficial Effects

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] Beneficial effect (1): The combustion rate catalyst provided by the present invention limits the movement of metal particles through a framework structure, thereby avoiding the agglomeration of metal-containing components. Moreover, after calcination in an air atmosphere / oxygen atmosphere, although the skeleton composed of carbon elements is no longer retained, a skeleton structure composed of metal oxides is formed. The skeleton structure still retains the pore structure characteristics of the MOFs material before calcination. The catalyst finally obtained has excellent catalytic performance.

[0067] Beneficial effect (2): The combustion rate catalyst provided by the present invention contains at least two kinds of metals (in the form of oxides). Compared with a catalyst having a skeleton structure composed of one metal oxide, the catalyst having a skeleton structure composed of at least two metal oxides has significantly improved catalytic performance.

[0068] Beneficial effect (3): Based on the above beneficial effect (2), the preferred combustion rate catalyst and preparation method thereof provided by the present invention contain at least two kinds of metals, and the difference in radius of the several kinds of metal ions is required to be no more than 17 pm;

[0069] This is one of the keys to solving the problem of low yield of bimetallic MOFs materials due to the different difficulty of combining bimetallic with ligands. For example, one preferred catalyst contains both copper and cobalt, Cu 2+ and Co 2+ have similar ionic radii (Cu 2+ : 72pm, Co 2+ ﹕74pm).

[0070] Beneficial effect (4): Based on any one of the above beneficial effects (1) to (3), or in combination thereof, the combustion rate catalyst and the preparation method thereof provided by the present invention utilize the principle that the spray drying process can obtain micro-nano spherical particles, and spray drying is used as a method for preparing MOFs materials to obtain hollow spherical shells with an average particle size of 2 to 4 μm. The spherical shells are composed of nano-scale MOFs material crystal particles and have a rich pore structure, and are used as calcined precursors of the combustion rate catalyst;

[0071] The above-mentioned precursor MOFs material is calcined in air / oxygen atmosphere to finally obtain a combustion rate catalyst with a skeleton structure mainly composed of metal oxides. The skeleton structure of the combustion rate catalyst still retains the pore structure characteristics of the MOFs material before calcination, and the finally obtained catalyst has excellent catalytic performance.

[0072] Beneficial effect (5): It should be emphasized that the present invention further preferably provides a combustion rate catalyst and a preparation method thereof, which further combines the beneficial effect (4) on the basis of the above beneficial effect (3);

[0073] The combustion rate catalyst contains at least two kinds of metals, and the difference in radius of the metal ions is required to be no more than 17 pm. The repeated and multiple spray drying technology described in beneficial effect (4) is further combined with the instantaneous evaporation of the solvent to combine the two metal salts with the ligands, thus overcoming the problem of low yield of bimetallic MOFs materials due to the different difficulty of combining the bimetallic with the ligands.

[0074] Beneficial effect (6): The method for preparing the combustion rate catalyst provided by the present invention breaks through the limitations of the solvent thermal method, such as long reaction time, complex post-processing and low yield. It adopts the spray drying method to quickly and continuously prepare MOFs material precursors, which is easy to scale up and more economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a SEM image of the spray-dried product Cu-MOFs in Example 1 and the calcined product SD-CuO;

[0076] Figure 2 This is a SEM image of the spray-dried product CuCo-MOFs in Example 2 and the calcined product SD-CuCoO;

[0077] Figure 3 This is the EDS image of the spray-dried product CuCo-MOFs in Example 2 and the calcined product SD-CuCoO;

[0078] Figure 4 The SEM image of the product ST-CuCoO after calcination of CuCo-MOFs obtained by the solvothermal method in Comparative Example 1;

[0079] Figure 5 This is the SEM image of the CuCo-MOFs material produced by the solvothermal method in Comparative Example 2;

[0080] Figure 6 This is the EDS image of the CuCo-MOFs material produced by the solvothermal method in Comparative Example 2;

[0081] Figure 7 This is the SEM image of Co-MOFs prepared by spray drying in Comparative Example 3, where: Figure 7 A is the SEM image of the product Co-MOFs prepared by spray drying method in Comparative Example 3 (after primary drying); Figure 7 B is the SEM image of the product Co-MOFs prepared by spray drying method in Comparative Example 3 (after secondary drying). DETAILED DESCRIPTION

[0082] The present disclosure may be more easily understood by reference to the following description in conjunction with the accompanying drawings and examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or shown herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise stated.

[0083] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.

[0084] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".

[0085] In the present disclosure, the singular forms of the articles "a," "an," and "the" also include the corresponding plural references, and a reference to a specific value includes at least that specific value unless the context clearly indicates otherwise. Thus, for example, a reference to "a substance" is a reference to at least one of that substance and equivalents thereof.

[0086] The terms including ordinal numbers such as "first" and "second" can be used to explain various components or fluids, but these components and fluids are not limited by these terms. Therefore, without departing from the teachings of the present disclosure, these terms are only used to distinguish the component / fluid from another component / fluid.

[0087] When items are described by using the conjunction terms "... and / or...," etc., the description should be understood to include any one of the associated listed items and all combinations of one or more thereof.

[0088] In general, the use of the term "about" indicates an approximate value that may vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values ​​can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to the values ​​stated in the range includes each value within the range.

[0089] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.

[0090] 【1】A method for preparing a burning rate catalyst

[0091] The preparation method comprises the following steps (S1) to (S3):

[0092] S1, preparing a mixed solution containing a metal source and an organic ligand;

[0093] S2, spraying the mixed solution 1 to obtain a dry product;

[0094] S3, subjecting the dried product 2 to high temperature treatment to obtain the combustion rate catalyst;

[0095] Step (S1): preparing a mixed solution containing a metal source and an organic ligand

[0096] Prepare the ingredients: The raw materials include a metal source and an organic ligand. The metal source and the organic ligand in a certain molar ratio are dissolved in the same solvent to obtain a metal source solution and a ligand solution. In fact, in the subsequent steps, the metal source and the organic ligand will undergo a process of forming a metal-organic framework (MOFs).

[0097] As the metal source, mainly the type of metal will have a significant impact on the catalytic ability of the combustion rate catalyst formed, and the metal is preferably selected from copper, cobalt, nickel, and iron. Usually, the metal source is a soluble salt of the corresponding type of metal. Taking cobalt as an example, the cobalt source used in the present invention can be, for example, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, and cobalt carbonate;

[0098] Alternatively, taking copper as an example, the copper source used in the present invention may include, for example, copper nitrate, copper chloride, copper sulfate, copper acetate, and copper carbonate;

[0099] From the perspective of improving the catalytic effect, it is preferred to introduce at least two metals into the combustion rate catalyst. For example, copper and cobalt are introduced to form a copper-cobalt bimetallic combustion rate catalyst, and the copper-cobalt bimetallic and organic ligands form MOFs materials. Compared with a single metal oxide, the introduction of the second metal can break through the catalytic limit of a single metal oxide, and the two produce a synergistic effect, thereby improving the catalytic effect.

[0100] Furthermore, from the perspective of the rationality of preparing bimetallic MOFs materials, the difference in ionic radius between the two metals should not exceed 17 pm; if the difference in ionic radius is too large, it will be difficult for metal 2 to occupy the metal site, and if it can be successfully coordinated, it will lead to lattice disorder, resulting in crystal defects and unstable crystal structure. Based on this, for example:

[0101] If the metal one is copper, the metal two preferably includes cobalt, iron and nickel, and the molar ratio of the two can be (0-10): (0-10), (0-10): (0-10); preferably (1-10): (1-10); more preferably (1-8): (1-8); further preferably (1-5): (1-5); and the most preferred ratio is 1:5.

[0102] As the "organic ligand", it is preferably trimesic acid; in fact, trimesic acid is a commonly used organic ligand for preparing MOFs materials.

[0103] There is no special requirement for the "solvent", which only needs to be able to dissolve the metal salt and trimesic acid at the same time, and examples thereof include:

[0104] As the "mixed solution", it is required to be formed by mixing the metal source solution and the ligand solution, and the two can be mixed by stirring. Mixed liquid The molar ratio of the metal source to the organic ligand is (3-1):(1-3), preferably (2.4-1):(1-1.2), and more preferably 2:1.

[0105] Step (S2): spraying the mixed solution to obtain a dry product;

[0106] As the method of "spray treatment", it can be carried out using an existing spray device, for example, a B-290 / B295 spray dryer can be cited; the key point is to carry out the " The following conditions need to be met when spraying:

[0107] Air flow speed 30~40m 3 / h;

[0108] The spray treatment inlet temperature is 170~190℃;

[0109] The feed rate is 1~2ml / min;

[0110] The actual volume flow rate of the material is 500~600 L / h.

[0111] For example, one of the more preferred options is:

[0112] Air velocity 38m 3 / h;

[0113] The spray treatment inlet temperature is 180°C;

[0114] The feed rate was 1.5 ml / min;

[0115] The actual volume flow rate of the material is 538L / h.

[0116] In fact, treating the mixed liquid by spray drying is the key to ensure that the MOFs material is nano-scale, and further ensures that the MOFs material has a spherical submicron shell structure; in addition, it is also the key to improving the preparation speed of MOFs material / burning rate catalyst. Based on this, it needs to be further clarified that the gas flow rate, spray treatment inlet temperature, feed rate and actual volume flow rate of the material in the above conditions will affect the sphericity of the MOFs material after drying and its burning rate catalytic performance; specifically:

[0117] If the gas flow rate is too high, the fine powder generated during the drying process will be carried by the gas to the filter cloth before it can settle in the cyclone separator, causing loss. If the gas flow rate is too low, it will take a long time to reduce the oxygen balance in the device to an appropriate range.

[0118] The inlet temperature will affect the yield of the MOFs material after drying and the shell morphology of the spherical shell. If the inlet temperature is too high, the surface concentration will increase faster and the shell will be formed earlier, resulting in low surface solute concentration, thinner shell wall, and easier volatilization and breaking of the shell; if the inlet temperature is too low, the solvent cannot evaporate fully, and the formation temperature of MOFs cannot be reached, resulting in low yield.

[0119] The feed rate will affect the yield and sphericity of the MOFs material after drying. If the feed rate is too high, the liquid will not have enough time to dry and react, resulting in insufficient drying and low yield. If the evaporation rate is too high, stress may form inside the particles. Once the stress is large enough, the shell of the particle will rupture and then collapse, resulting in irregular particle shape. If the feed rate is too low, the liquid will react at the nozzle to generate MOFs or evaporate and precipitate, thereby clogging the nozzle.

[0120] In addition, in S2, performing at least two spray drying operations is the key to ensuring the yield of the MOFs material / combustion rate catalyst product. The S2 operation steps for reference are as follows:

[0121] The mixed solution obtained in S1 is sprayed to obtain a dry product;

[0122] preparing a second mixed solution containing a dry product;

[0123] The mixed solution 2 is sprayed to obtain a dry product again.

[0124] Step (S3): subjecting the dried product to high temperature treatment to obtain the combustion rate catalyst;

[0125] The method of the "high temperature treatment" is not particularly limited as long as a reaction environment having a certain temperature and an oxygen-containing reaction atmosphere can be provided, and a conventionally known method can be used.

[0126] For example, the combustion rate catalyst can be obtained by using a tubular furnace, introducing an air atmosphere / oxygen atmosphere, and subjecting the dried product to high-temperature treatment.

[0127] The temperature of the high temperature treatment is preferably 300-600° C. and the treatment time is 1-3 h.

[0128] The "oxygen atmosphere" can be achieved by introducing a gas containing oxygen or a direct air atmosphere.

[0129] It is preferred that the dried product obtained in S2 be washed before performing step (S3).

[0130] The "washing" method is not particularly limited as long as it can remove unreacted raw materials in the product; for example, ethanol can be used for washing three times.

[0131] After washing, the product is dried. The drying method is not particularly limited, and any conventionally known drying method may be used. For example, the product may be dried in a dryer or a vacuum oven at a temperature not exceeding 100° C. for 8 to 12 hours.

[0132] 【2】Combustion rate catalyst

[0133] The burning rate catalyst comprises: a metal oxide having a pore structure;

[0134] As the combustion rate catalyst, it can also selectively satisfy any one of the following (I) to (VI) or any combination of several of the following; (I) to (VI) are:

[0135] (I) As the metal oxide, the metal element thereof includes any one of copper, cobalt, nickel and iron, or two or more of them;

[0136] (II) Calculated according to the proportion of elements, the weight ratio of metal elements to oxygen elements is (2~2.6): (0.8~1);

[0137] (III) As the metal oxide, it includes any one of copper, cobalt, nickel, and iron, or oxides of two or more metals;

[0138] (IV) As the metal, it includes metal 1 and metal 2, and the difference in ionic radius between the metal 1 and the metal 2 does not exceed 17 pm;

[0139] The metal is selected from one or more of copper and cobalt;

[0140] The metal is selected from one or more of cobalt, nickel and iron.

[0141] (V) As the metal, it includes metal one and metal two, and the molar ratio of the metal one to the metal two is (0-10): (0-10);

[0142] (VI) As the burning rate catalyst, it is spherical; the sphere has an average particle size of 2 to 4 μm; the sphere includes a nanoscale metal oxide;

[0143] (VII) As the burning rate catalyst, it is preferable to use the above 【1】A method for preparing a burning rate catalyst , prepared.

[0144] (VIII) As the combustion rate catalyst, it is used as a combustion rate catalyst of ammonium perchlorate.

[0145] 【3】A solid propellant;

[0146] The solid propellant contains the above 【2】Combustion rate catalyst Any of the burning rate catalysts described in; or 【1】One Preparation method of burning rate catalyst , a burning rate catalyst prepared by any of the methods;

[0147] or,

[0148] The solid propellant contains the above 【2】Combustion rate catalyst Any of the burning rate catalysts; or 【1】One Preparation method of burning rate catalyst , and, ammonium perchlorate.

[0149] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The essential characteristics and remarkable effects of the present invention can be reflected from the following examples, and the described embodiments are part of the embodiments of the present invention, rather than all the embodiments, and therefore, they do not limit the present invention in any way, and those skilled in the art make some non-essential improvements and adjustments based on the content of the present invention, which all belong to the protection scope of the present invention.

[0150] Example 1

[0151] The burning rate catalyst preparation method of this embodiment is as follows:

[0152] 7.248 g (36 mmol) Cu(NO3)2·3H2O and 3.150 g (15 mmol) H3BTC were placed in two beakers respectively, 35 mL of DMF was added to each beaker, and the mixture was mixed in a beaker after ultrasonic dissolution. The mixture was stirred on a constant temperature magnetic stirrer for 30 min to fully mix the two solutions.

[0153] The mixed solution was pumped into the B-290 / B-295 spray dryer and dry gas was introduced. When the oxygen content in the device dropped below 5.8%, heating was started and the temperature was kept at 1.5 mL min. -1 Feed rate, 538L·h -1 The spray drying was carried out at an actual volume flow rate of and an inlet temperature of 180°C; after the spraying was completed, the sample was collected and then dispersed in DMF, and the spray drying was repeated again.

[0154] After spraying, the blue sample was collected, and then the powder was dispersed in 60 mL of ethanol and centrifuged for 3 times. The obtained product was dried at 80° C. for 6 h to obtain the Cu-MOFs precursor.

[0155] The precursor was placed in a tube furnace, and the heating rate was set to 5°C / min, the calcination temperature was set to 300°C, and the temperature was kept for 2 hours to obtain a calcined product. The calcined product in air atmosphere was a copper metal oxide skeleton, which was recorded as SD-CuO.

[0156] Figure 1 This is a SEM image of the spray-dried Cu-MOFs material in Example 1 after calcination. It can be seen from the image that the combustion rate catalyst is spherical with an average particle size of 2 to 4 μm.

[0157] Example 2

[0158] The combustion rate catalyst of this embodiment is spherical; the sphere has an average particle size of 2 to 4 μm; in addition,

[0159] The catalyst is a skeleton structure composed of copper oxide and cobalt oxide, and the skeleton structure has a pore structure similar to that of MOFs material;

[0160] Calculated according to the ratio of elements, the weight ratio of the metal element to the oxygen element is 2.57:1;

[0161] The catalyst can be used as a solid propellant, especially in combination with ammonium perchlorate.

[0162] The preparation method of the burning rate catalyst of this embodiment is as follows:

[0163] 1.45 g (6 mmol) Cu(NO3)2·3H2O and 8.731 g (30 mmol) Co(NO3)2·6H2O were ultrasonically dissolved in 35 ml DMF, and 3.150 g (15 mmol) H3BTC was ultrasonically dissolved in 35 ml DMF. The two solutions were then mixed and magnetically stirred for 30 min to ensure that the two solutions were fully mixed.

[0164] The mixed solution was pumped into the B-290 / B-295 spray dryer and dry gas was introduced. When the oxygen content in the device dropped below 5.8%, heating was started and the temperature was kept at 1.5 mL min. -1 Feed rate, 538L·h -1 The spray drying was carried out at an actual volume flow rate of and an inlet temperature of 180°C; after the spraying was completed, the sample was collected and then dispersed in DMF, and the spray drying was repeated again.

[0165] After spraying, the blue sample was collected, and then the powder was dispersed in 60 mL of ethanol and centrifuged for 3 times. The obtained product was dried at 80 ° C for 6 h to obtain the CuCo-MOFs precursor. The precursor was placed in a tube furnace, set the heating rate of 5 ° C / min, the calcination temperature of 300 ° C, and kept warm for 2 h to obtain the calcined product.

[0166] The calcination product under air atmosphere is metallic copper oxide and metallic cobalt oxide skeleton, which is denoted as SD-CuCoO.

[0167] Figure 2 This is a SEM image of the spray-dried CuCo-MOFs material (Cu:Co=1:5) after calcination in Example 2. It can be seen from the image that the combustion rate catalyst prepared by this method is spherical, has a rough surface, and has abundant catalytic active sites; Figure 3 This is the EDS graph of the calcined product. It can be seen from the graph that the content of metal elements is 72 wt% and the content of oxygen elements is 28 wt%.

[0168] Comparative Example 1

[0169] The burning rate catalyst preparation method of this comparative example is as follows:

[0170] The proportion of raw materials used is the same as in Example 2. 0.242 g (1 mmol) Cu(NO3)2·3H2O and 1.45 g (5 mmol) Co(NO3)2·6H2O are ultrasonically dissolved in 15 ml DMF, and 0.525 g (2.5 mmol) H3BTC is ultrasonically dissolved in 15 ml DMF and mixed, and ultrasonication is continued for 10 minutes.

[0171] The mixture was then placed in a 45 mL polytetrafluoroethylene-lined stainless steel hydrothermal autoclave. The autoclave was sealed and placed in a forced air oven, heated to 85°C at a heating rate of 1.0°C / min and maintained for 20 hours before naturally cooling to room temperature. The reaction product was separated by suction filtration with anhydrous ethanol, washed several times, and dried at 80°C overnight to obtain the CuCo-MOFs precursor.

[0172] The precursor was placed in a tubular furnace, and a heating rate of 5°C / min and a calcination temperature of 300°C were set. The temperature was kept at this temperature for 2 hours to obtain a calcined product.

[0173] The calcination product under air atmosphere is metallic copper oxide and metallic cobalt oxide skeleton, which is denoted as ST-CuCoO.

[0174] Figure 4 This is the SEM image of the calcined product of the solvothermal method CuCo-MOFs material (Cu:Co=1:5) in Comparative Example 1. It can be seen from the figure that in the air atmosphere, the tetrahedral structure of Cu-MOF is retained, and the metal generates oxides in situ to form a skeleton structure.

[0175] Comparative Example 2

[0176] The burning rate catalyst preparation method of this comparative example is as follows:

[0177] 1.21 g (5 mmol) Cu(NO3)2·3H2O and 1.45 g (5 mmol) Co(NO3)2·6H2O were ultrasonically dissolved in 15 ml DMF, and 0.525 g (2.5 mmol) H3BTC was ultrasonically dissolved in 15 ml DMF, mixed, and continued ultrasonically for 10 min.

[0178] The mixture was then placed in a 45 mL polytetrafluoroethylene-lined stainless steel hydrothermal autoclave. The autoclave was sealed and placed in a forced air oven, heated to 85°C at a heating rate of 1.0°C / min and maintained for 20 hours before naturally cooling to room temperature. The reaction product was separated by suction filtration with anhydrous ethanol, washed several times, and dried at 80°C overnight to obtain CuCo-MOFs (Cu:Co=1:1).

[0179] Figure 5 This is the SEM of the CuCo-MOFs material in this comparative example. It can be seen from the figure that the MOFs material prepared by the hydrothermal method has a regular octahedral crystalline morphology with edges and corners. When applied to the field of energetic materials, hot spots are often concentrated at the edges and corners, which increases the sensitivity and leads to safety problems.

[0180] Figure 6This is the EDS image of the CuCo-MOFs material in the comparative example. When the copper-cobalt molar ratio is 1:1, the Cu-MOFs regular octahedral structure is basically maintained, but after EDS element scanning, it is found that when the Cu salt and C salt are 1:1, the Co element content is low. This shows that copper salt is easier to coordinate with trimesic acid, and the copper salt concentration should not be too high, which is not conducive to the formation of copper-cobalt bimetallic MOFs materials.

[0181] Comparative Example 3

[0182] 8.731 g (30 mmol) of Co(NO3)2·6H2O and 3.150 g (15 mmol) of H3BTC were placed in two beakers, 35 mL of DMF was added to each beaker, and the mixture was mixed in a beaker after ultrasonic dissolution. The mixture was stirred on a constant temperature magnetic stirrer for 30 min to fully mix the two solutions.

[0183] The mixed solution was pumped into the B-290 / B-295 spray dryer and dry gas was introduced. When the oxygen content in the device dropped below 5.8%, heating was started and the temperature was kept at 1.5 mL min. -1 Feed rate, 538L·h -1 The experiment was carried out at an actual volume flow rate of 1000 μg / cm2 and an inlet temperature of 180°C. After the spraying was completed, the sample was collected and dispersed in DMF, and the spray drying was repeated again. A small amount of the sample was taken for direct post-treatment.

[0184] After spraying, the pink sample was collected, and then the powder was dispersed in 60 mL of ethanol and centrifuged for 3 times. The obtained product was dried at 80 ° C for 6 h to obtain Co-MOFs.

[0185] Among them, the Co-MOFs that were spray-dried once were recorded as SD-CoO-MOFs-1, and the Co-MOFs that were spray-dried twice were recorded as SD-CoO-MOFs-2

[0186] Figure 7 This is the SEM image of Co-MOFs prepared by spray drying in Comparative Example 3, where: Figure 7 A is the product SD-Co-MOFs-1 after one drying. Figure 7 B is SD-Co-MOFs-2 after secondary drying.

[0187] After comparison, it was found that the spherical structure of the product SD-Co-MOFs-2 after the second spray drying was more complete, and the spherical shell was composed of nano-scale MOFs crystal particles, indicating that the number of spray drying can affect the formation of the spherical structure of the product and the integrity of the spherical structure;

[0188] After calculation, the product yield after the first spray drying is 28%~20%, and the yield after the second spray drying is 73%~62%, which greatly improves the yield.

[0189] The specific surface area of ​​the product SD-Co-MOFs-1 after one drying was found to be 950.28 m 2 / g, and the specific surface area of ​​the secondary dried product SD-Co-MOF-2 is 1572.9m 2 / g, indicating that the number of spray drying can affect the specific surface area of ​​the product.

[0190] Based on the Co-MOFs product obtained by the above spray drying, high-temperature calcination was performed in an air atmosphere according to the method in Example 2. The calcined product of SD-Co-MOFs-1 was SD-CoO-1; the calcined product of SD-Co-MOFs-2 was SD-CoO-2.

[0191] Example 4

[0192] In this example, the catalytic activity of the combustion rate catalyst obtained above to AP was studied.

[0193] Table 1 Comparison of catalytic activity of burning rate catalysts on AP

[0194]

[0195] According to the table, the single metal oxide catalyst SD-CuO calcined with Cu-MOFs material as the precursor in air atmosphere has a great thermal effect on the AP catalytic process.

[0196] Compared with the single metal oxide catalyst SD-CuO, the bimetallic oxide catalyst SD-CuCoO and the bimetallic catalyst SD-CuCo showed better catalytic performance. The bimetallic catalyst SD-CuCoO advanced the AP exothermic peak by 81.49°C, increased the exothermic heat by 5.8 times, and reduced the activation energy by nearly half.

[0197] Compared with SD-CoO-1, SD-CoO-2 has a higher specific surface area and its catalytic activity is greatly improved, which advances the high-temperature decomposition peak of AP from 372.28℃ to 339.40℃ and increases the heat release from 1192.22 J / g to 1213.34 J / g.

[0198] Compared with the bimetallic oxide catalyst ST-CuCoO (the bimetallic MOFs material prepared by traditional hydrothermal method is used as a precursor, and the product bimetallic catalyst ST-CuCoO is obtained by calcining in an air atmosphere), the bimetallic oxide catalyst SD-CuCoO (the bimetallic MOFs material prepared by spray drying is used as a precursor, and the product bimetallic catalyst SD-CuCoO is obtained by calcining in an air atmosphere) also exhibits better catalytic performance.

[0199] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A burning rate catalyst, characterized in that The burning rate catalyst is obtained by high temperature treatment of a metal organic framework material, and the burning rate catalyst comprises: A metal oxide framework having a pore structure; Calculated according to the proportion of elements, the weight ratio of metal elements to oxygen elements is (2~2.6): (0.8~1); in, The high temperature treatment has a treatment temperature of 300-500°C and an oxygen atmosphere; The metal organic framework material is obtained by: a mixed solution containing a metal source and an organic ligand, which is sprayed; the molar ratio of the metal source to the organic ligand is (3-1): (3-1); The number of spray treatments is ≥ 2 times; The metal includes metal one and metal two, and the difference in ionic radius between the metal one and the metal two does not exceed 17 pm; The metal is selected from one or both of copper and cobalt; The metal is selected from one, two or three of cobalt, nickel and iron; The organic ligand is trimesic acid.

2. A method for preparing a burning rate catalyst as claimed in claim 1, characterized in that: S1, preparing a mixed solution containing a metal source and an organic ligand; the molar ratio of the metal source and the organic ligand is (3-1): (3-1); The metal includes metal one and metal two, and the difference in ionic radius between the metal one and the metal two does not exceed 17 pm; The amount of the metal source added must satisfy the molar ratio of metal one to metal two of (1-10): (1-10); The metal is selected from one or both of copper and cobalt; The metal is selected from one, two or three of cobalt, nickel and iron; S2, spraying the mixed solution to obtain a dry product; S3, subjecting the dried product to high temperature treatment to obtain the burning rate catalyst; in, In S1, the organic ligand is trimesic acid; In S2, the number of spray treatments is ≥ 2 times; In S3, the temperature of the high temperature treatment is 300-500° C. and the atmosphere is an oxygen atmosphere.

3. The method for preparing a burning rate catalyst according to claim 2, characterized in that: In S2, the process parameters of the spray treatment are as follows: Air flow speed 30~40m 3 / h; The spray treatment inlet temperature is 170~190℃; The feed rate is 1~2ml / min.

4. The method for preparing a burning rate catalyst according to any one of claims 2 to 3, characterized in that: In S3, the high temperature treatment time is 1 to 3 hours.

5. A solid propellant, characterized in that: The solid propellant contains the burning rate catalyst as claimed in claim 1; or the burning rate catalyst prepared by the method as claimed in any one of claims 2 to 4; or, The solid propellant contains the burning rate catalyst as claimed in claim 1; or the burning rate catalyst prepared by the method according to any one of claims 2 to 4; and ammonium perchlorate.

6. Use of the burning rate catalyst according to claim 1, or the burning rate catalyst prepared by the method according to any one of claims 2 to 4, characterized in that: Used as a combustion rate catalyst for ammonium perchlorate.

Citation Information

Patent Citations

  • Preparation method and application of carbon-based copper-cobalt oxide nanosheet catalyst

    CN107442125A